2016
DOI: 10.1017/s0144686x16000696
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of loneliness and different types of social isolation of rural-living older adults in the United Kingdom

Abstract: Loneliness and social isolation are recognised, conceptually-distinct threats to health and wellbeing in older age but limited evidence is available on their predictors in rural populations. This study performed logistical regression modelling to explore the predictors of loneliness, isolation from one's family and isolation from one's community in 884 British rural-living older adults (57.9% female, mean age 71.5 [SD 8.1] years) within the Grey and Pleasant Land dataset. While 13 per cent of participants repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 69 publications
3
44
0
2
Order By: Relevance
“…Older people. Our findings echoed a lot of rural studies literature (De Koning et al, 2017;Kelly et al, 2019) which shows that "Loneliness is a huge problem" for older rural residents. As a result, "a lot of widows and widowers .…”
Section: A Rural Needs Frameworksupporting
confidence: 85%
“…Older people. Our findings echoed a lot of rural studies literature (De Koning et al, 2017;Kelly et al, 2019) which shows that "Loneliness is a huge problem" for older rural residents. As a result, "a lot of widows and widowers .…”
Section: A Rural Needs Frameworksupporting
confidence: 85%
“…Using the same measure, Scharf and de Jong Gierveld reported a prevalence of loneliness of 13% for severe loneliness in 3 urban disadvantaged areas in Britain (London, Liverpool and Manchester) and 43% as moderately lonely for a sample of 497 participants aged 60-96 (mean age = 71.6) [17]. For rural areas in the UK, De Koning et al reported a prevalence of 9% for loneliness for those aged 65+ in 6 rural areas of England which approximates to the national norm [30] and is comparable to findings reported by Wenger and Burholt (2004) in a rural area of North Wales [31].…”
Section: Factors Related To Loneliness In Later Lifementioning
confidence: 97%
“…Using the same measure, Scharf and de Jong Gierveld reported a prevalence of loneliness of 13% (severe) and 43% (moderate) for 497 participants aged 60-96 (mean age = 71.6) living in 3 urban disadvantaged areas in Britain (London, Liverpool and Manchester) [28]. De Koning et al reported a prevalence of 9% for loneliness for those aged 65+ in 6 rural areas of England [29]. This approximates to the national norm [5] and is comparable with findings reported by Wenger and Burholt (2004) in a rural area of North Wales [30].…”
Section: The Geography Of Lonelinessmentioning
confidence: 99%